Free Flap Reconstruction in Patients with Traumatic Injury of the Forefoot - Shin Hyuk Kang; Jeongseok Oh; Seok Chan Eun (Journal of Trauma and Injury)
Many techniques have been developed for reconstruction of the hand; however, less attention has been paid to foot reconstruction techniques. In particular, reconstruction of the forefoot and big toe has been considered a minor procedure despite the importance of these body parts for standing and walking. Most of the weight load on the foot is concentrated on the forefoot and big toe, whereas the other toes have a minor role in weight bearing. Moreover, the forefoot and big toe are important for maintaining balance and supporting the body when changing directions. Recently, attention has been focused on the aesthetic appearance and functional aspects of the body, which are important considerations in the field of reconstructive surgery. In patients for whom flap reconstruction in the forefoot and big toe is planned, clinicians should pay close attention to flap survival as well as functional and cosmetic outcomes of surgery. In particular, it is important to assess the ability of the flap to withstand functional weight bearing and maintain sufficient durability under shearing force. Recovery of protective sensation in the forefoot area can reduce the risk of flap loss and promote rapid rehabilitation and functional recovery. Here, we report our experience with two cases of successful reconstruction of the forefoot and big toe with a sensate anterolateral thigh flap, with a review of the relevant literature.